Water-repellent protective film with double-layer composite structure and preparation method of water-repellent protective film
Through the double-layer composite structure of the water-repellent protective film, low-polymerization material is used to quickly fill the circuit fine grooves, high-polymerization material provides support, and combined with the water-repellent layer of fluorine-containing compounds and silicone compounds, the problems of short-term water-repellent performance and pattern collapse in the existing technology are solved, efficient pattern protection is achieved, and the yield of semiconductor manufacturing is significantly improved.
Patent Information
- Application Number
- CN202511121668.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-12
- Publication Date
- 2025-09-09
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing water-repellent protective films have difficulty maintaining long-term water-repellency in the complex semiconductor manufacturing environment and cannot effectively prevent the collapse of high-aspect ratio circuit patterns. In particular, pattern collapse is easily caused during the cleaning process, affecting production efficiency and yield.
The water-repellent protective film adopts a double-layer composite structure, including a support layer and a water-repellent layer. The support layer is compounded by low-polymerization degree and high-polymerization degree materials. The low-polymerization degree material quickly penetrates and fills the fine grooves of the circuit, and the high-polymerization degree material provides high-strength support; the water-repellent layer adopts a molecular-level hybrid system of fluorine-containing compounds and silicone compounds to form a water-repellent layer with ultra-low surface energy.
It significantly improves the water-repellent properties of the protective film and its ability to support and protect circuit patterns, reduces the occurrence rate of pattern collapse by more than 90%, and improves the yield rate of chip manufacturing.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of semiconductor manufacturing and precision electronic device protection, and particularly relates to a water-repellent protective film with a double-layer composite structure capable of effectively preventing circuit pattern collapse and a preparation method thereof. Background Art
[0002] In the fields of networks, digital home appliances, etc., semiconductor equipment is rapidly developing towards high performance, high functionality and low power consumption. To meet this demand, the miniaturization of circuit patterns is constantly advancing. However, as the degree of miniaturization of circuit patterns deepens, the problem of pattern collapse becomes increasingly prominent, becoming a key bottleneck restricting the development of semiconductor manufacturing. In the semiconductor equipment manufacturing process, the cleaning process accounts for 30-40% of the overall process, and its main purpose is to remove contaminants such as particles and metal impurities. However, as the circuit patterns of semiconductor equipment become miniaturized, the aspect ratio of the pattern continues to increase. In the process after cleaning or rinsing, when the gas-liquid interface passes through the pattern, it is very easy to cause pattern collapse. Once pattern collapse occurs, not only may the pattern design need to be changed, but the production yield will also be greatly reduced, seriously affecting production efficiency and product quality. Therefore, an effective solution is urgently needed.
[0003] Currently, forming a water-repellent protective film on the pattern surface has been proven to be an effective way to prevent pattern collapse. This method requires replacing the cleaning solution with a chemical solution for forming a water-repellent protective film when the pattern surface is not dry. For example, Japanese Patent Publication No. 2017-063179 discloses a surface treatment agent comprising a silylating agent and a nitrogen-containing heterocyclic compound without silicon atoms, which can effectively prevent the collapse of inorganic / resin patterns. In addition, CN111742391A further proposes a chemical solution for forming a water-repellent protective film, which comprises a silylating agent, a nitrogen-containing compound, and an organic solvent. The basicity adaptability of the catalyst is improved by introducing a nitrogen-containing compound with a specific structure.
[0004] However, existing water-repellent protective films have many shortcomings. Traditional protective films mostly use a single chemical coating material, whose water-repellent properties are difficult to maintain in the complex semiconductor manufacturing environment and have poor compatibility with new semiconductor materials. Although some protective films can reduce surface tension to a certain extent, they cannot provide sufficient structural support for circuit patterns with high aspect ratios and still cannot effectively prevent pattern collapse. Therefore, it is necessary to develop a new type of water-repellent protective film that not only has excellent water-repellent properties but also enhances the structural protection of circuit patterns, fundamentally solving the problem of pattern collapse. Summary of the Invention
[0005] In response to the deficiencies in the prior art, the present invention provides a water-repellent protective film with a double-layer composite structure and a method for preparing the same. Through a unique material combination and structural design, the present invention significantly improves the water-repellent properties of the protective film, its ability to support and protect circuit patterns, and the filling rate of fine gap circuits, effectively preventing pattern collapse. A method for preparing the protective film is provided to ensure uniform material compounding and stable structural molding, thereby realizing large-scale production. The invention provides an efficient and reliable pattern protection solution for the semiconductor manufacturing industry.
[0006] To achieve the above technical objectives, the present invention adopts the following technical solution: a double-layer composite water-repellent protective film, comprising a support layer and a water-repellent layer provided on the surface of the support layer, wherein:
[0007] (1) The support layer comprises a low-polymerization material (I) and a high-polymerization material (II).
[0008] H-(A) i -BH (Ⅰ)
[0009] In the structural formula (I), H is selected from a hydrogen atom or a hydroxyl group; A is selected from a polycaprolactone segment (CH2)5-CO-O, a polylactic acid segment CH(CH3)-CO-O, a polycarbonate segment OC(=O)-OR, R is selected from an aliphatic or aromatic group; B is selected from a carboxyl group or an amino group; the degree of polymerization i ranges from 1 to 50.
[0010] Z-(C) m -DZ (Ⅱ)
[0011] In the structural formula (II), Z is selected from hydroxyl, carboxyl, amino, methyl, and ethyl; C is selected from polycaprolactone segment (CH2)5-CO-O, polyimide segment CO-C6H4-CO-NH-C6H4-NH, polyurethane segment O-R 1 -O-CO-NH-R 2 -NH-CO, R 1 is a polyether or polyester segment, R 2 is a diisocyanate residue; D is selected from a single bond, a sulfonic acid group -SO3H, and an epoxy group -CH(O)CH2; the degree of polymerization m ranges from 51 to 200;
[0012] (2) The water-repellent layer comprises at least one of the compounds represented by structural formulas (III) and (IV),
[0013] [CH2=C(R 3 )-COO-R 4 -F] n (III)
[0014] In the structural formula (III), R 3 is selected from a hydrogen atom or a methyl group; R4 C6-C 18 Alkyl, preferably perfluorooctyl, the degree of polymerization n of the polyester ranges from 1 to 5,
[0015] [(R 4 )3Si-O-] j -[CH2=C(R 5 )-COO-R 6 -F] k (IV)
[0016] In the structural formula (Ⅳ), R 4 is selected from methyl or ethyl, and the degree of polymerization j ranges from 1 to 5; R 5 is selected from a hydrogen atom or a methyl group; R 6 C4-C in which some or all of the hydrogen atoms are replaced by fluorine atoms 12 Alkyl; k is the degree of polymerization of the fluorinated acrylate segment, ranging from 1 to 5.
[0017] Furthermore, the low polymerization degree material (I) is selected from:
[0018] α,ω-dihydroxypolycaprolactone with a degree of polymerization i=20, α-carboxy-ω-hydroxypolycaprolactone with a degree of polymerization i=30, α-amino-ω-hydroxypolycaprolactone with a degree of polymerization i=15, α,ω-dicarboxypolycaprolactone with a degree of polymerization i=40, α,ω-diaminopolycaprolactone with a degree of polymerization i=25, α,ω-dipropylpolycaprolactone with a degree of polymerization i=32;
[0019] or α-propyl-ω-carboxyl polylactic acid with a degree of polymerization i=10, α-amino-ω-propyl polylactic acid with a degree of polymerization i=42, α,ω-dipropyl polylactic acid with a degree of polymerization i=28, α-methyl-ω-carboxyl polylactic acid with a degree of polymerization i=36, α-ethyl-ω-amino polylactic acid with a degree of polymerization i=14;
[0020] Or α-propyl-ω-hydroxypolycyclohexene carbonate with a degree of polymerization i=20, α-carboxy-ω-propyl polyphenyl carbonate with a degree of polymerization i=40, α-amino-ω-methyl polycyclohexene carbonate with a degree of polymerization i=24, α,ω-diethyl polyphenyl carbonate with a degree of polymerization i=30, α-methacryloyl-ω-amino polycyclohexene carbonate with a degree of polymerization i=18.
[0021] Furthermore, the high polymerization degree material (II) is selected from:
[0022] α-propyl-ω-hydroxypolycaprolactone with a degree of polymerization m=65, α-amino-ω-methylpolycaprolactone with a degree of polymerization m=100, α-amino-ω-propyl polycaprolactone with a degree of polymerization m=105, α,ω-dipropyl polycaprolactone with a degree of polymerization m=145, α-hydroxy-ω-epoxypolycaprolactone with a degree of polymerization m=85, and α-carboxy-ω-sulfonic acid polycaprolactone with a degree of polymerization m=125;
[0023] or α-propyl-ω-hydroxy polyimide with a degree of polymerization m=75, α-methyl-ω-ethyl polyimide with a degree of polymerization m=115, α-carboxy-ω-propyl polyimide with a degree of polymerization m=155, α,ω-dihydroxysulfonic acid polyimide with a degree of polymerization m=95, α-amino-ω-epoxy polyimide with a degree of polymerization m=175;
[0024] Or α-propyl-ω-hydroxy polyether polyurethane with a polymerization degree of m=60, α,ω-dipropyl polyester polyurethane with a polymerization degree of m=100, α-hydroxy-ω-sulfonic acid polyether polyurethane with a polymerization degree of m=140, α-carboxy-ω-epoxy polyester polyurethane with a polymerization degree of m=80, α-amino-ω-methyl polyether polyurethane with a polymerization degree of m=180.
[0025] Furthermore, the mass ratio of the low-polymerization-degree material (I) to the high-polymerization-degree material (II) in the support layer is in the range of 25:75 to 60:40.
[0026] The present invention also provides a method for preparing the above-mentioned double-layer composite water-repellent protective film, comprising the following steps:
[0027] S1, preparation of supporting layer polymer: adding low-polymerization degree material (I) and high-polymerization degree material (II) in proportion to a reactor containing a solvent, heating to 60±10°C and stirring to completely dissolve; then adding methyl methacrylate and a catalyst, heating to 70±5°C, and reacting under nitrogen for 4-8 hours. The obtained product solution is precipitated in anhydrous ethanol, filtered, and vacuum dried to obtain a composite supporting layer polymer;
[0028] S2, preparation of a water-repellent layer polymer: adding a solvent to a reaction vessel, and under nitrogen protection, adding trimethylsiloxane and perfluorooctyl acrylate in proportion and stirring until completely dissolved, then adding azobisisobutyronitrile (AIBN) as an initiator, and continuously stirring at 70±5°C for 4-8 hours to cause a free radical polymerization reaction. After the reaction is completed, the reaction solution is introduced into petroleum ether for precipitation. The precipitate collected by filtration is washed with petroleum ether several times to remove residual solvent and unreacted monomers, and then vacuum dried to obtain a trimethoxysiloxane-perfluorooctyl acrylate water-repellent layer polymer;
[0029] S3, pouring the composite supporting layer polymer obtained in step S1 into ethanol, stirring at 40±5°C to completely dissolve it to obtain a supporting layer solution; adding the trimethoxysiloxane-perfluorooctyl acrylate water-repellent layer polymer obtained in step S2 into dichloromethane, stirring at 40±5°C to completely dissolve it to obtain a water-repellent layer solution; slowly adding the water-repellent layer solution to the supporting layer solution under stirring to obtain a protective film composition solution with a solid content of 35-50% and no stratification or precipitation.
[0030] Furthermore, in step S1, when the low polymerization degree material (I) is a polycaprolactone oligomer, the solvent is selected as N,N-dimethylformamide (DMF); when the low polymerization degree material (I) is a polylactic acid oligomer, the solvent is selected as dichloromethane; when the low polymerization degree material (I) is a polyurethane oligomer, the solvent is selected as tetrahydrofuran (THF).
[0031] 7 Furthermore, in step S1, the catalyst is p-toluenesulfonic acid, dibutyltin dilaurate, and stannous octoate, and the added amount thereof accounts for 0.1-2% of the total mass of the reaction monomers.
[0032] Furthermore, in step S2, when synthesizing the water-repellent layer polymer of structural formula (III), the solvent is selected from ethyl acetate and dichloromethane; when synthesizing the water-repellent layer polymer of structural formula (IV), the solvent is toluene, xylene, or tetrahydrofuran.
[0033] Beneficial effects: Compared with the prior art, the water-repellent protective film of the present invention realizes multiple protections for the circuit pattern through the double-layer structure design of the support layer and the water-repellent layer. The support layer is compounded by low-polymerization degree and high-polymerization degree materials, wherein the low-polymerization degree gives the material excellent fluidity due to its shorter molecular chain, and can quickly penetrate and fill the fine grooves of the high aspect ratio circuit in a very short time, achieving efficient filling; the high-polymerization degree long-chain molecules have a slower diffusion speed due to their long molecular chain, and are enriched near the external area of the high aspect ratio channel to form a high-strength support structure, which effectively enhances the overall tensile strength of the film layer, can stably carry the circuit pattern, evenly disperse the external force, and significantly reduce the stress concentration phenomenon; the water-repellent coating repels water with extremely low surface energy, reducing direct contact between the liquid and the pattern. The composite structure works together to reduce the pattern collapse rate of the high aspect ratio circuit pattern by more than 90% in the simulated cleaning process, greatly improving the chip manufacturing yield. DETAILED DESCRIPTION
[0034] The present invention is further illustrated below in conjunction with specific synthesis examples. It should be understood that these synthesis examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the present invention, modifications of various equivalent forms of the present invention made by those skilled in the art all fall within the scope defined by the claims attached to this application.
[0035] The present invention provides a water-repellent protective film with a double-layer composite structure, which comprises: (A) a support layer: an innovative two-component high and low polymerization degree compound system is used, which is synergistically constructed by short chains and long chains in different mass ratios. The short-chain component, due to its low viscosity, can achieve efficient filling of gaps in fine circuits with high aspect ratios, while the long-chain component gives the material excellent mechanical properties, achieving a combination of high permeability and structural rigidity; (B) a water-repellent layer: a molecular-level hybrid system of fluorine-containing compounds and organosilicon compounds is used, and the fluorine-containing segments achieve ultra-low surface energy (contact angle > 110°), while the organosilicon segments enhance the flexibility of the film layer. This layer forms a gradient transition structure with the bottom layer through interfacial chemical bonding, which maintains superhydrophobic properties while ensuring interlayer bonding strength.
[0036] The main components of the double-layer composite water-repellent protective film of the present invention are described in detail below:
[0037] 1. Bottom support layer
[0038] The bottom support layer material is used to form a support structure on the surface of a wafer having a high aspect ratio circuit pattern, and mainly comprises a low-polymerization material (I) and a high-polymerization material (II), wherein:
[0039] (1) Low degree of polymerization material, which has the following general structural formula,
[0040] H-(A) i -BH (I), in formula (I),
[0041] H represents the terminal hydrogen atom or active group such as hydroxyl group of the molecular chain. Its activity helps the material to undergo cross-linking or grafting reaction with other components in subsequent reactions, thereby enhancing the bonding strength and overall performance of the materials.
[0042] A represents a repeating structural unit. Different low-polymer materials have different structures. For example, in the case of polycaprolactone oligomers, A = (CH2)5-CO-O; in polylactic acid oligomers, A = CH(CH3)-CO-O; and in polycarbonate oligomers, A = OC(=O)-OR (where R is an aliphatic or aromatic group). These repeating structural units determine the material's basic chemical properties, physical properties, and molecular chain morphology. i represents the degree of polymerization, and its specific value depends on the material's characteristics and application requirements. The i value directly affects the molecular chain length, which in turn influences the material's fluidity, viscosity, and other properties. For example, a lower i value results in a shorter molecular chain, improving material fluidity and facilitating filling complex structures; a higher i value results in a longer molecular chain, providing a certain degree of mechanical strength.
[0043] B is a connecting group or a specific functional structural unit. In some materials, B can be a chemical bond (such as a single bond), which plays the role of connecting repeating units. In some functional oligomers, B can introduce specific functional groups (such as carboxyl, amino, etc.) to give the material special properties, such as reactivity, hydrophilicity or compatibility with other materials.
[0044] 2. As preferred examples, specific examples of the general formula (I) include: α,ω-dihydroxypolycaprolactone (i=20), α-carboxy-ω-hydroxypolycaprolactone (i=30), α-amino-ω-hydroxypolycaprolactone (i=15), α,ω-dicarboxypolycaprolactone (i=40), α,ω-diaminopolycaprolactone (i=25), α,ω- Dipropyl polycaprolactone (i=32), α-propyl-ω-carboxy polylactic acid (i=10), α-amino-ω-propyl polylactic acid (i=42), α,ω-dipropyl polylactic acid (i=28), α-methyl-ω-carboxy polylactic acid (i=36), α-ethyl-ω-amino polylactic acid (i=14), α-propyl-ω-hydroxypolycyclohexene carbonate (i=20), α-carboxy-ω-propyl polyphenyl carbonate (i=40), α-amino-ω-methyl polycyclohexene carbonate (i=24), α,ω-diethyl polyphenyl carbonate (i=30), α-methacryloyl-ω-aminopolycyclohexene carbonate (i=18), etc.
[0045] (2) High polymer materials with a high degree of polymerization have the following general structural formula:
[0046] Z-(C) m -DZ, (II), in formula (II),
[0047] Z represents the terminal group of the molecular chain, which can be an active group such as hydroxyl (-OH), carboxyl (-COOH), or amino (-NH2), or an inert capping group such as methyl (-CH3) or ethyl (-C2H5). Active terminal groups can participate in subsequent reactions such as cross-linking and grafting, further optimizing material properties; inert capping groups stabilize the molecular chain, preventing degradation or adverse reactions under specific conditions.
[0048] C represents a repeating structural unit. Different types of high-polymer polymers have distinct structures. For polycaprolactone polymers, C is (CH2)5-CO-O; for polyimide polymers, C is CO-C6H4-CO-NH-C6H4-NH; and for polyurethane polymers, C is O-R1-O-CO-NH-R2-NH-CO (where R1 represents a polyether or polyester segment and R2 represents a diisocyanate residue). These repeating structural units fundamentally determine the chemical and thermodynamic properties of the material, as well as the aggregate structure of the molecular chain. m represents the degree of polymerization; its specific value should be determined flexibly based on the material's specific application and performance requirements. The value of m is directly related to the length of the molecular chain. Higher m values result in longer and more entangled chains, significantly improving the material's mechanical strength, toughness, and wear resistance, but may also reduce its flowability. Lower m values result in shorter molecular chains, improving its flowability, but reducing its mechanical properties.
[0049] D is a connecting group or functional structural unit. In some materials, D can be a simple chemical bond (such as a single bond) used to connect repeating units. In functional polymers, D can introduce special functional groups (such as sulfonic acid group -SO3H, epoxy group -CH(O)CH2, etc.) to give the material special functions such as conductivity, antistatic properties, and chemical corrosion resistance, or enhance the compatibility and interfacial bonding between the material and other substances.
[0050] 3. As preferred examples, specific examples of the general formula (II) include: α-propyl-ω-hydroxypolycaprolactone (m=65), α-amino-ω-methylpolycaprolactone (m=100), α-amino-ω-propyl polycaprolactone (m=105), α,ω-dipropyl polycaprolactone (m=145), α-hydroxy-ω-epoxy polycaprolactone (m=85), α-carboxyl-ω-sulfonic acid polycaprolactone (m=125), α-propyl-ω-hydroxy polyimide (m=75), α-methyl-ω-ethyl polyimide ( m=115), α-carboxy-ω-propyl polyimide (m=155), α,ω-dihydroxysulfonic acid polyimide (m=95), α-amino-ω-epoxy polyimide (m=175), α-propyl-ω-hydroxy polyether polyurethane (m=60), α,ω-dipropyl polyester polyurethane (m=100), α-hydroxy-ω-sulfonic acid polyether polyurethane (m=140), α-carboxy-ω-epoxy polyester polyurethane (m=80), α-amino-ω-methyl polyether polyurethane (m=180), etc.
[0051] (3) Selection of supporting layer solvent
[0052] During the preparation of support layer materials, the solvent, catalyst, and reaction conditions must be flexibly and precisely controlled based on the characteristics of the material system. Solvent selection: For polyester-based support layer materials, such as polycaprolactone oligomer and polymer composite systems, N,N-dimethylformamide (DMF) can be used as a solvent. Its excellent solubility can effectively promote the dispersion and dissolution of polymerizable functional monomers such as methyl methacrylate, facilitating the smooth progress of grafting or copolymerization reactions. If a polylactic acid oligomer and polycaprolactone polymer combination system is used, dichloromethane, with its moderate solubility and volatilization rate, can ensure sufficient material dissolution and facilitate rapid volatilization of the solvent during the subsequent film formation process. When synthesizing polyurethane-based support layer materials, using acetone as a solvent during the prepolymer reaction stage can significantly reduce the viscosity of the system and ensure more uniform mixing of the reaction materials. In the subsequent film formation stage, tetrahydrofuran (THF) can ensure the formation of a uniform and stable solution system due to its good compatibility with polyurethane.
[0053] (4) Catalyst selection
[0054] Catalyst Selection: For polyester polymerization reactions, such as the grafting reaction of polycaprolactone with acrylates and the copolymerization of polycarbonate oligomers with functional monomers, organic acid catalysts such as p-toluenesulfonic acid are ideal. They effectively catalyze esterification and grafting reactions, and the catalyst dosage generally accounts for 0.1-1% of the total monomer weight. For polyurethane synthesis, organometallic catalysts such as dibutyltin dilaurate and stannous octoate can effectively catalyze the reaction between isocyanates and polyols, playing a key role in polyurethane prepolymer synthesis and chain extension reactions. Their dosage is generally controlled at 0.3-2% of the total monomer weight, and the specific dosage needs to be optimized based on the reaction scale and desired reaction rate.
[0055] (5) Selection of synthesis conditions
[0056] Reaction Temperature and Time: Polyester polymerization reactions, such as the grafting of polycaprolactone oligomers with polymers or methyl methacrylate, are best conducted at a temperature between 60-80°C and 3-8 hours. This ensures sufficient reaction time while preventing degradation of the polycaprolactone molecular chain due to excessive temperatures. In the synthesis of polyurethanes, the prepolymer synthesis stage is maintained at a temperature of 70-90°C for 2-4 hours to fully react with the isocyanate and polyol to form the prepolymer. The chain extension reaction is then slightly lowered to 60-70°C for 1-3 hours to ensure smooth reaction between the chain extender and the prepolymer, forming a polyurethane polymer with a specific molecular weight and structure. Heating or refluxing can accelerate the reaction, but the temperature must be carefully monitored to prevent polymer degradation or unwanted side reactions due to temperature runaway.
[0057] Content control: Calculated based on the solid content excluding solvents, the polymer content in the support layer material composition needs to be finely adjusted according to actual needs and material types. For polyester-based bottom support layer materials, if a polycaprolactone-polylactic acid mixed system is used, the polymer content is usually controlled at 10-70% by weight. This range can not only ensure that the material has good mechanical properties such as tensile strength and flexibility, but also meet the requirements of solution viscosity for processing techniques such as spin coating, ensuring the formation of a uniform and continuous support layer on the chip surface. In polyurethane-based bottom support layer materials, such as a composite system of polyether polyurethane and polyester polyurethane, the polymer content is preferably 20-80% by weight. This content range allows the material to achieve a good balance between flexibility and rigidity, provide a stable and reliable support effect for the circuit pattern, effectively disperse external forces, and reduce stress concentration.
[0058] 2. Surface water-repellent layer
[0059] The water-repellent layer polymer of the present invention comprises at least one of the compounds represented by structural formulas (III) and (IV).
[0060] [CH2=C(R 3 )-COO-R 4 -F] n (III)
[0061] In the structural formula (III), R 3 is selected from a hydrogen atom or a methyl group; R 4 C6-C 18 The alkyl group is preferably a perfluorooctyl group, and the degree of polymerization n of the polyester ranges from 1 to 5. The high electronegativity and small atomic radius of the fluorine element significantly reduce the surface energy of the material, and the water contact angle can reach over 110°.
[0062] [(R 4 )3Si-O-] j -[CH2=C(R 5 )-COO-R 6 -F] k (IV)
[0063] In the structural formula (Ⅳ), R 4 is selected from methyl or ethyl, and the degree of polymerization j ranges from 1 to 5; R 5 is selected from a hydrogen atom or a methyl group; R 6 C4-C in which some or all of the hydrogen atoms are replaced by fluorine atoms 12 alkyl; k is the degree of polymerization of the fluorinated acrylate segment, ranging from 1 to 5. This hybrid material combines the flexibility of silicone and the superhydrophobicity of the fluorinated segment, with a water contact angle of 100°-120°.
[0064] Specific examples of the surface water-repellent layer compound may include, for example, perfluorohexyl acrylate, perfluorohexyl methacrylate, perfluorooctyl acrylate, perfluorooctyl methacrylate, perfluorodecyl acrylate, perfluorodecyl methacrylate, perfluorododecyl acrylate, perfluorododecyl methacrylate, perfluorotetradecyl acrylate, perfluorotetradecyl methacrylate, perfluorohexadecyl acrylate, perfluorohexadecyl methacrylate, perfluorooctadecyl acrylate, perfluorooctadecyl methacrylate, trimethylsiloxy perfluorobutyl acrylate, trimethylsiloxy perfluorobutyl meth ... Siloxy perfluorohexyl acrylate, trimethylsiloxy perfluorohexyl methacrylate, trimethylsiloxy perfluorooctyl acrylate, trimethylsiloxy perfluorooctyl methacrylate, trimethylsiloxy perfluorodecyl acrylate, trimethylsiloxy perfluorodecyl methacrylate, trimethylsiloxy perfluorododecyl acrylate, trimethylsiloxy perfluorododecyl methacrylate, triethylsiloxy perfluorobutyl acrylate, triethylsiloxy perfluorobutyl methacrylate, triethylsiloxy perfluorohexyl acrylate, triethylsiloxy perfluorohexyl methacrylate, triethylsiloxy perfluorooctyl methacrylate, etc.
[0065] In the process of preparing the surface water-repellent layer, the selection of solvents, catalysts and reaction conditions need to be precisely controlled according to the material properties. In view of the special structure of fluorine-containing compounds and organosilicon-fluorine-containing hybrid compounds, commonly used solvents need to have good solubility and moderate volatility. For the fluorine-containing acrylate compound represented by formula (III), ethyl acetate and dichloromethane are ideal solvent choices. Ethyl acetate can effectively dissolve the fluorine-containing monomer and initiator in the reaction stage, while dichloromethane is suitable for the subsequent film-forming process. Its strong volatility helps to quickly form a uniform water-repellent film layer; for the organosilicon-fluorine-containing hybrid compound of formula (IV), toluene, xylene mixed solvent or tetrahydrofuran can simultaneously dissolve the organosilicon monomer and the fluorine-containing acrylate monomer, thereby promoting the hybrid reaction.
[0066] The choice of catalyst depends on the type of reaction. In free radical polymerization reactions, benzoyl peroxide (BPO) and azobisisobutyronitrile (AIBN) are often used as initiators, with their dosage generally controlled at 0.3-2% of the total monomer weight. For example, in the synthesis of perfluorooctyl acrylate, AIBN decomposes at 60-75°C to produce free radicals, initiating polymerization. If the hybridization reaction involves organosilicon segments and fluorinated acrylate segments, an appropriate amount of dibutyltin dilaurate can be added as a catalyst, at approximately 0.1-0.5% of the total monomer weight, to promote the formation of silicon-oxygen bonds and the smooth progress of the hybridization reaction.
[0067] Reaction temperature and time have a critical influence on the water-repellent properties of the surface water-repellent layer material. The reaction temperature of fluorinated acrylate compounds is usually controlled at 60-80°C, and the reaction time is 4-8 hours. Within this temperature range, the decomposition of the fluorinated monomer can be effectively avoided while ensuring that the reaction proceeds fully. For the synthesis of organosilicon-fluorinated hybrid compounds, the reaction temperature can be appropriately increased to 70-90°C, and the reaction time can be extended to 6-10 hours to ensure that the organosilicon segment and the fluorinated acrylate segment are fully hybridized. The reaction process can be accelerated by heating or refluxing, but the temperature must be strictly monitored to prevent the degradation of the fluorinated segment or the side reactions of the organosilicon segment due to excessive temperature.
[0068] In the composition of the surface water-repellent layer, the content of the water-repellent layer compound, calculated based on the solid content excluding solvents, needs to be optimized according to the actual application scenario. For a pure fluorine-containing compound system, in order to ensure excellent water-repellent properties, its content is usually controlled at 60-90% by weight; and for an organosilicon-fluorine-containing hybrid compound system, considering the contribution of the organosilicon segment to flexibility and the improvement of the water repellency by the fluorine-containing segment, the content of the hybrid compound is preferably 50-80% by weight. In semiconductor manufacturing scenarios where water repellency is extremely demanding, the content of fluorine-containing compounds or hybrid compounds can be increased to 80-90% by weight; if both flexibility and water repellency need to be taken into account, the content of organosilicon-fluorine-containing hybrid compounds can be controlled at 65-75% by weight, thereby forming a protective film with both high water repellency and good flexibility on the surface of the semiconductor substrate, effectively isolating moisture from the circuit pattern, while adapting to the deformation requirements of the substrate.
[0069] 3. Organic solvents
[0070] The water-repellent protective film composition of the present invention is prepared in liquid form by thoroughly mixing the components of the support layer and the water-repellent layer with a solvent. The amount of solvent used significantly affects the film-forming effect. The solid content (i.e., the support layer and water-repellent layer components, excluding the solvent) is preferably controlled at 10-60% by weight, calculated based on the total weight of the composition. Within this range, the solution can be guaranteed to have suitable coating fluidity, ensuring uniform spreading on the surface of the semiconductor substrate, while also maintaining the dispersion stability of the support layer and water-repellent layer materials. For example, when the support layer utilizes a composite system of low-polymerization degree and high-polymerization degree polycaprolactone, too low a solid content may result in insufficient mechanical strength of the film layer; too high a solid content will result in excessive solution viscosity, affecting its penetration and filling effect in high-aspect-ratio structures. For the fluorinated acrylate compound in the water-repellent layer, an appropriate solid content helps to form a continuous and dense nanoscale rough structure, ensuring low surface energy water-repellent properties.
[0071] The present invention has broad adaptability in terms of solvent selection. The core requirement is that the solvent must be able to fully dissolve the components of the support layer and the water-repellent layer, and must be chemically stable to avoid adverse reactions with the materials. For support layer materials containing polyester polymers (such as polycaprolactone and polylactic acid), alcohols (such as ethanol), ethers (such as tetrahydrofuran), and esters (such as ethyl acetate) can effectively dissolve the polymers without disrupting their molecular chain structure, ensuring the fluidity of low-polymerization materials and the entanglement stability of high-polymerization materials. When the support layer contains high-glass-transition-temperature materials such as polycarbonate, highly polar solvents such as dichloromethane and dimethyl sulfoxide can improve dissolution efficiency.
[0072] For the fluorinated acrylate compounds and silicone modifiers of the water-repellent layer, aromatic hydrocarbon solvents such as toluene and xylene have good solubility for fluorinated groups, which helps the fluorinated segments to enrich on the surface during the film formation process and form a low surface energy interface; while glycol ether ester solvents such as propylene glycol methyl ether acetate can not only dissolve silicone components, but also regulate the surface roughness of the film during volatilization, thereby promoting the formation of nano-scale water-repellent structures.
[0073] More specific examples of the solvent include methanol, ethanol, tetrahydrofuran, dioxane, methyl cellosolve acetate, ethyl cellosolve acetate, ethyl acetoacetate, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, propylene glycol dimethyl ether, propylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol dimethyl ether, diethylene glycol ethyl methyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, dipropylene glycol dimethyl ether, dipropylene glycol diethyl ether, propylene glycol monomethyl ... Alcohol methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol propyl ether acetate, dipropylene glycol methyl ether acetate, propylene glycol butyl ether acetate, toluene, dimethylbenzene, methyl ethyl ketone, 4-hydroxy-4-methyl-2-pentanone, cyclopentanone, cyclohexanone, 2-heptanone, gamma-butyrolactone, ethyl 2-hydroxypropionate, ethyl 2-hydroxy-2-methylpropionate, ethyl acetate, butyl acetate, ethyl lactate, butyl lactate, N,N-dimethylformamide, N,N-dimethylacetamide, N-Methylpyrrolidone etc.Preferred ethanol of the present invention, tetrahydrofuran, dichloromethane, dimethyl sulfoxide, ethyl acetate are as solvent.These solvents can be used alone or composite according to different preparation requirements. For example, in the spin coating process, ethanol and ethyl acetate are mixed in a specific ratio. This can not only utilize the rapid volatilization characteristics of ethanol to accelerate the initial film formation, but also use ethyl acetate to adjust the drying rate of the solution to avoid cracks or unevenness in the film layer due to excessively rapid solvent volatilization. For high-aspect-ratio structures that require deep penetration and filling, the combination of dichloromethane and dimethyl sulfoxide can enhance the solution's solubility for the support layer and water-repellent layer materials, ensuring that the liquid fully infiltrates the fine grooves to form a complete and continuous protective film.
[0074] 4. About the water-repellent protective film with double-layer composite structure
[0075] In this invention, the water-repellent protective film based on a dual-layer composite structure is constructed by constructing a multi-layer composite structure on the surface of a substrate such as a wafer, significantly reducing the substrate's surface wettability and imparting excellent water-repellent properties. The protective film is composed of a support layer and a surface water-repellent layer. Each layer is specifically designed and synthesized to achieve different levels of surface energy reduction and enhanced water-repellency.
[0076] 5. About Chips
[0077] Generally speaking, to obtain a wafer with a fine concavo-convex pattern on its surface, first, after applying a resist to a smooth wafer surface, the resist is exposed through a resist mask and the exposed or unexposed resist is etched away to produce a resist layer with the desired concavo-convex pattern. Alternatively, a resist layer with a concavo-convex pattern can be obtained by pressing a patterned mold against the resist layer. Next, the wafer is etched. In this case, the wafer surface corresponding to the concave portions of the resist pattern is selectively etched. Finally, by stripping the resist layer, a wafer with a fine concavo-convex pattern can be obtained.
[0078] 6. About the surface treatment of the chip
[0079] In the present invention, as long as a cleaning device of a chemical solution or cleaning liquid that can maintain the above-mentioned liquid state on the concave-convex pattern of the wafer is used, the cleaning method of the wafer is not particularly limited. As the cleaning method of the wafer, the following can be listed: a single-wafer cleaning method, in which a rotary cleaning device can be used, by keeping the wafer in horizontal rotation and supplying cleaning liquid to the center, using centrifugal force to evenly cover the surface of the wafer with the cleaning liquid. This method can accurately control the contact time and strength of the cleaning liquid with the film layer, avoiding damage to the support layer and the water-repellent layer. The support layer is compounded from materials with different degrees of polymerization. The low-polymerization material gives it good fluidity, and the high-polymerization material provides mechanical strength. The gentle action of rotary cleaning can prevent the support layer structure from being damaged by external forces, ensuring its stable support for the circuit pattern; at the same time, rotary cleaning can maintain the water-repellent properties of the water-repellent layer with its low surface energy. If batch cleaning is adopted, when immersing multiple wafers in the cleaning tank, the flow rate and direction of the cleaning liquid must be strictly controlled to prevent collisions between the wafers, so as to avoid rupture of the support layer membrane or wear of the water-repellent layer surface, affecting the overall protective performance.
[0080] When supplying a protective film-forming agent, chemical solution, or cleaning fluid to the concave areas of the wafer's concave-convex pattern, the material properties of the support layer and water-repellent layer must be carefully considered. The low-polymerization-degree material in the support layer has high fluidity. To ensure the solution effectively infiltrates and fills the concave areas while preserving the structure of the high-polymerization-degree material, a low-surface-tension solution or finely atomized aerosol is preferred. For water-repellent layers composed of fluorinated acrylate compounds, using an organic solvent with good compatibility with fluorides as a carrier allows the solution to fully infiltrate the concave areas, forming a continuous, uniform water-repellent film and enhancing the water-repellent effect.
[0081] When cleaning after forming the protective film, the cleaning time needs to be strictly controlled. From the perspective of removing surface particles and impurities, the cleaning time should be no less than 15 seconds to ensure that the contaminants are fully removed; but if the cleaning time exceeds 10 minutes, it may have an adverse effect on the support layer and the water-repellent layer. Some polymers in the support layer may swell due to long-term immersion, resulting in a decrease in mechanical strength, affecting the support for the circuit pattern; the fluorinated chain segments of the water-repellent layer may undergo orientation changes, reducing the surface water repellency, or damaging the surface nanostructure. The cleaning solution preferably uses an organic solvent with good compatibility with the support layer and water-repellent layer materials, such as ethyl acetate, which can effectively dissolve impurities without destroying the chemical cross-linking network of the support layer and the molecular arrangement structure of the water-repellent layer.
[0082] The drying process is crucial to the ultimate performance of the protective film. Spin drying utilizes centrifugal force to remove surface liquid, resulting in rapid drying without thermal damage. This method is suitable for mechanically sensitive support layer materials, preventing structural deformation. IPA vapor drying utilizes the volatility and low surface tension of isopropyl alcohol to effectively remove residual liquid from tiny recesses while preserving the nanoscale rough structure of the water-repellent layer, ensuring water-repellent properties. During the drying process, the temperature must be controlled based on the thermal stability of the material to prevent high-temperature degradation or structural rearrangement of heat-sensitive materials in the support and water-repellent layers, ensuring the water-repellent film's excellent protective properties in fields such as semiconductor manufacturing.
[0083] The present invention is described in more detail below by way of examples. However, these examples are provided to illustrate the present invention, and the scope of the present invention is not limited thereto. In the following examples, the detection methods of the various performance indicators are as follows:
[0084] (1) Determination of weight average molecular weight:
[0085] It was determined by gel permeation chromatography (GPC) using polystyrene standards.
[0086] (2) Evaluation of the contact angle of the protective film formed on the wafer surface:
[0087] About 2 μL of pure water was placed on the wafer surface having the protective film formed thereon, and the angle (contact angle) between the water droplet and the wafer surface was measured using a contact angle meter (CA-X model, manufactured by Kyowa Interface Science Co., Ltd.).
[0088] (3) Support layer tensile strength test:
[0089] First, dumbbell-shaped bottom support layer samples were cut from the water-repellent protective film. Their dimensions met the requirements for tensile testing of plastics in the national standard GB / T 1040.3-2006, with a gauge length of 25 mm, a width of 6 mm, and a thickness equal to the actual thickness of the bottom support layer. Five replicate samples were prepared for each test to ensure data reliability.
[0090] Before the test, an electronic universal material testing machine was used to calibrate the equipment to ensure the accuracy of the force sensor and displacement sensor. The fixture was installed on the testing machine and the position of the fixture was adjusted to ensure that the sample could be evenly stressed. Next, the two ends of the sample were fixed in the upper and lower fixtures of the testing machine to ensure that the installation was firm and without distortion. The test speed was set to 5 mm / min, the testing machine was started, and the sample was subjected to a tensile test. During the test, the equipment automatically recorded the tensile force and displacement data until the sample broke. After the test was completed, the maximum tensile force (F) at the time of sample fracture was extracted from the data. The tensile strength was calculated according to the formula: Tensile strength = F / S. Among them, S is the initial cross-sectional area of the sample gauge section (S = gauge section width × gauge section thickness). Finally, the test results of the five parallel samples were averaged to obtain the tensile strength of the underlying support layer.
[0091] (4) Fill rate test:
[0092] First, a simulated circuit trench structure with a specified aspect ratio is fabricated on a silicon wafer. After applying a protective film and curing, cross-sectional samples are obtained using focused ion beam sectioning. The sample cross-section is observed using a field emission scanning electron microscope. High-resolution images are captured at multiple locations, and quantitative analysis is performed using image processing software. The fill fraction (η) is calculated using the formula: η = (Afilled / Atotal) × 100%, where Afilled represents the pixel area of the filled region in the SEM image, and Atotal represents the total pixel area of the trench structure. To verify the accuracy of the results, three-dimensional topography can be measured using X-ray reflectivity or confocal microscopy. The test environment temperature must be maintained at 23±1°C, and repeated measurements are performed at the same location to ensure data reliability. This method objectively evaluates the fill performance of the protective film on microstructures, providing a basis for material optimization.
[0093] Example 1
[0094] S1. Synthesis of α,ω-dihydroxy polycaprolactone oligomer (i=20)
[0095] 1.45 g of 1,4-butanediol and 50 mL of DMF were added to a dry 250 mL four-necked flask. After stirring to completely dissolve the 1,4-butanediol, a condenser and thermometer were installed, and nitrogen was introduced to replace the air in the flask for 15 minutes to eliminate oxygen interference. Subsequently, 0.25 g of stannous octoate was added, and after stirring and uniform dispersion, 50 g of ε-caprolactone was slowly added. The temperature was raised to 120°C, and a ring-opening polymerization reaction was carried out under continuous stirring and nitrogen protection for 2 hours. After the reaction, the reaction solution was cooled to room temperature and transferred to a rotary evaporator. The DMF solvent was removed at 80°C under reduced pressure. The crude product was precipitated with petroleum ether, filtered through a Buchner funnel, and dried in a vacuum drying oven at 60°C for 24 hours to obtain α,ω-dihydroxy polycaprolactone oligomer (i=20).
[0096] S2. Synthesis of α-amino-ω-methyl polycaprolactone polymer (m=100)
[0097] 2.3 g of ω-amino-ω'-methyl-1,6-hexanediol and 200 mL of DMF were added to a dry 500 mL four-necked flask. After stirring to completely dissolve the mixture, a condenser and a thermometer were installed, and nitrogen was introduced to replace the air in the flask for 20 minutes to eliminate oxygen. Subsequently, 0.5 g of stannous octoate was added, and after stirring and dispersing evenly, 100 g of ε-caprolactone was slowly added. The temperature was raised to 120°C, and a ring-opening polymerization reaction was carried out under continuous stirring and nitrogen protection for 8 hours. After the reaction was completed, the mixture was cooled to room temperature and transferred to a rotary evaporator. The DMF solvent was removed at 100°C under reduced pressure. The crude product was precipitated with anhydrous ether, filtered with a Buchner funnel, and dried in a vacuum drying oven at 60°C for 24 hours to obtain α-amino-ω-methyl polycaprolactone polymer (m=100).
[0098] S3. Preparation of support layer polymer: α,ω-dihydroxy polycaprolactone (i=20) + α-amino-ω-methyl polycaprolactone (m=100) complex
[0099] The α,ω-dihydroxypolycaprolactone (i=20) and α-amino-ω-methylpolycaprolactone (m=100) prepared above were added to a 1000 mL four-necked flask in a mass ratio of 1:1, 300 mL of DMF was added, the temperature was raised to 60°C and stirred until completely dissolved, 50 g of methyl methacrylate and 0.5 g of p-toluenesulfonic acid were added, the temperature was raised to 70°C and the reaction was carried out under nitrogen protection for 6 hours, the product solution was poured into 1000 mL of anhydrous ethanol for precipitation, filtered with a Buchner funnel, and the precipitate was dried in a vacuum drying oven at 50°C for 12 hours.
[0100] S4, synthetic trimethylsiloxane-perfluorooctyl acrylate
[0101] 200 mL of dichloromethane was added to a 500 mL four-necked flask equipped with a stirrer, a condenser, and a nitrogen conduit as a solvent. Nitrogen was introduced to replace the air in the flask for 15 minutes, and 60 g of trimethylsiloxane and 140 g of perfluorooctyl acrylate were added in sequence and stirred to fully dissolve. After the system stabilized, 0.5 g of azobisisobutyronitrile (AIBN) was added as an initiator. The reaction apparatus was placed in a constant temperature water bath at 70°C and stirred continuously at 200 rpm under nitrogen protection for free radical polymerization for 6 hours. After the reaction, the reaction solution was slowly poured into a large amount of petroleum ether for precipitation to precipitate the compound. The precipitate was collected by filtration and washed with petroleum ether several times to remove the residual solvent and unreacted monomers. The product was then placed in a vacuum drying oven and dried at 40°C for 12 hours to obtain trimethylsiloxane-perfluorooctyl acrylate.
[0102] S5. Preparation of chemical solution for forming protective film
[0103] Accurately weigh 50 g of the supporting layer polymer prepared in step S3 and 80 g of the trimethylsiloxane-perfluorooctyl acrylate water-repellent layer compound prepared in step S4, measure 120 g of ethanol and 180 g of dichloromethane as solvents, and check the specifications and purity of the raw materials; slowly pour the polycaprolactone composite supporting layer polymer into ethanol, use a magnetic stirrer to stir at 40 ° C and 200 rpm until completely dissolved, and at the same time, add trimethylsiloxane-perfluorooctyl acrylate to dichloromethane and stir under the same conditions until dissolved; slowly pour the water-repellent layer compound solution into the supporting layer polymer solution. The protective film was prepared by adding the protective film composition solution with a solid content of 43% and no stratification and precipitation into the liquid and gently stirring with a glass rod; a pipette was used to draw up the solution and dripped it onto the center of the semiconductor substrate fixed on the sample stage of the spin coater, and the spin coater speed was set to 3000 rpm and the coating time was 30 seconds in a clean environment; after coating, it was dried at room temperature for 1 hour and then placed in a vacuum drying oven at 80°C for 2 hours to solidify the protective film; the final test results showed that the water contact angle reached 114°, the tensile strength of the support layer was 25 MPa, and the filling rate was 98.6%, which can meet the protection needs of semiconductor manufacturing.
[0104] Examples 2-6 and Comparative Examples 1-3
[0105] The water-repellent protective film compositions of this example and comparative example were each prepared in the same manner as in Example 1, except that the types and / or contents of the corresponding components were changed as shown in Table 1 below.
[0106] As shown in Table 1, chemical solutions were prepared in the same manner as in Example 1, and wafer surface treatment was performed, followed by evaluation. The examples demonstrate the effects of different formulations (e.g., replacing the support layer with polylactic acid or polyurethane, and the water-repellent layer with other fluorinated materials) on tensile strength, fill factor, and contact angle. The comparative examples demonstrate the importance of various factors for the performance of the protective film by deliberately varying key conditions (e.g., using only a single polymerized compound in the support layer and omitting a fluorinated silicone material in the water-repellent layer). For example, Comparative Examples 1 and 2 demonstrate the effects of single low-polymerization-degree materials and single high-polymer materials on fill factor and tensile strength. Low-polymerization-degree materials achieve efficient fill efficiency due to their short molecular chains and lack of entanglement. However, tensile strength decreases with decreasing polymerization degree, and a single oligomer support layer cannot meet the compressive strength requirements of semiconductor processes. Although high-polymerization materials can improve mechanical strength through molecular chain entanglement, the viscosity also increases with the increase of polymerization degree, resulting in increased flow resistance in high aspect ratio grooves and a filling rate reduced by about 60% compared with the compound system; Comparative Example 3 verifies the key influence of the fluorine / silicone structure on water repellency (contact angle), and the embodiment shows an excellent water repellency imparting effect in comparison with it.
[0107] Table 1
[0108]
[0109] As can be seen from the performance results in Table 1, in the water-repellent protective film based on the double-layer composite structure, the surface water-repellent layer and the support layer are interdependent and work synergistically to give the protective film excellent water repellency, high filling rate and reliable support capacity. The rational design and precise preparation of the materials of each layer are the key to achieving high-performance protective films. The lack or insufficiency of the performance of any layer will lead to a significant decline in the performance of the overall protective film, which cannot meet the stringent requirements for chip protection in high-end fields such as semiconductor manufacturing.
[0110] The innovation of this invention lies in providing a water-repellent protective film with a double-layer composite structure. This dual-layer design, comprised of a support layer and a surface water-repellent layer, achieves superior comprehensive protective performance through material synergy. The support layer utilizes a gradient degree of polymerization (DPG) compounding technique, where low-DP components penetrate nanoscale pores to efficiently fill high-aspect-ratio structures, while high-DP components enhance support stability for wafer microcircuit patterns. The surface water-repellent layer utilizes a fluorinated acrylate / silicone hybrid system, exhibiting ultra-low surface energy and a water contact angle ≥110°. This invention addresses the issue of insufficient performance from a single material through structural synergy.
[0111] With the above-mentioned ideal synthesis examples according to the present invention as inspiration, and through the above description, relevant personnel can make various changes and modifications without departing from the scope of the technical concept of this invention. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. A double-layer composite water-repellent protective film, characterized in that: It comprises a support layer and a water-repellent layer provided on the surface of the support layer, wherein: (1) The support layer comprises a low-polymerization material (I) and a high-polymerization material (II). H-(A) i -B-H (Ⅰ) In the structural formula (I), H is selected from hydrogen atom or hydroxyl group; A is selected from polycaprolactone chain segment , polylactic acid segment , polycarbonate segments , R is selected from aliphatic or aromatic groups; B is selected from carboxyl and amino groups; the degree of polymerization i ranges from 1 to 50, Z-(C) m -D-Z (Ⅱ) In the structural formula (II), Z is selected from hydroxyl, carboxyl, amino, methyl, and ethyl; C is selected from a polycaprolactone segment , polyimide segment , polyurethane segment , R 1 is a polyether or polyester segment, R 2 is a diisocyanate residue; D is selected from a single bond, a sulfonic acid group -SO3H, and an epoxy group -CH(O)CH2; the degree of polymerization m ranges from 51 to 200; (2) The water-repellent layer comprises at least one of the compounds represented by structural formulas (III) and (IV), [CH2=C(R 3 )-COO-R 4 -F] n (Ⅲ) In the structural formula (III), R 3 is selected from a hydrogen atom or a methyl group; R 4 C6-C 18 Alkyl, the degree of polymerization n of polyester ranges from 1 to 5; [(R 4 )3Si-O-] j -[CH2=C(R 5 )-COO-R 6 -F] k (Ⅳ) In the structural formula (Ⅳ), R 4 is selected from methyl or ethyl, and the degree of polymerization j ranges from 1 to 5; R 5 is selected from a hydrogen atom or a methyl group; R 6 Some or all of the hydrogen atoms are replaced by fluorine atoms Alkyl; k is the degree of polymerization of the fluorinated acrylate segment, ranging from 1 to 5.
2. The double-layer composite water-repellent protective film according to claim 1, characterized in that: The low polymerization degree material (I) is selected from: α,ω-dihydroxypolycaprolactone with a degree of polymerization i=20, α-carboxy-ω-hydroxypolycaprolactone with a degree of polymerization i=30, α-amino-ω-hydroxypolycaprolactone with a degree of polymerization i=15, α,ω-dicarboxypolycaprolactone with a degree of polymerization i=40, α,ω-diaminopolycaprolactone with a degree of polymerization i=25, α,ω-dipropylpolycaprolactone with a degree of polymerization i=32; or α-propyl-ω-carboxyl polylactic acid with a degree of polymerization i=10, α-amino-ω-propyl polylactic acid with a degree of polymerization i=42, α,ω-dipropyl polylactic acid with a degree of polymerization i=28, α-methyl-ω-carboxyl polylactic acid with a degree of polymerization i=36, α-ethyl-ω-amino polylactic acid with a degree of polymerization i=14; Or α-propyl-ω-hydroxypolycyclohexene carbonate with a degree of polymerization i=20, α-carboxy-ω-propyl polyphenyl carbonate with a degree of polymerization i=40, α-amino-ω-methyl polycyclohexene carbonate with a degree of polymerization i=24, α,ω-diethyl polyphenyl carbonate with a degree of polymerization i=30, α-methacryloyl-ω-amino polycyclohexene carbonate with a degree of polymerization i=18.
3. The double-layer composite water-repellent protective film according to claim 1, characterized in that: The high polymerization degree material (II) is selected from: α-propyl-ω-hydroxypolycaprolactone with a degree of polymerization m=65, α-amino-ω-methylpolycaprolactone with a degree of polymerization m=100, α-amino-ω-propyl polycaprolactone with a degree of polymerization m=105, α,ω-dipropyl polycaprolactone with a degree of polymerization m=145, α-hydroxy-ω-epoxypolycaprolactone with a degree of polymerization m=85, and α-carboxy-ω-sulfonic acid polycaprolactone with a degree of polymerization m=125; or α-propyl-ω-hydroxy polyimide with a degree of polymerization m=75, α-methyl-ω-ethyl polyimide with a degree of polymerization m=115, α-carboxy-ω-propyl polyimide with a degree of polymerization m=155, α,ω-dihydroxysulfonic acid polyimide with a degree of polymerization m=95, α-amino-ω-epoxy polyimide with a degree of polymerization m=175; Or α-propyl-ω-hydroxy polyether polyurethane with a polymerization degree of m=60, α,ω-dipropyl polyester polyurethane with a polymerization degree of m=100, α-hydroxy-ω-sulfonic acid polyether polyurethane with a polymerization degree of m=140, α-carboxy-ω-epoxy polyester polyurethane with a polymerization degree of m=80, α-amino-ω-methyl polyether polyurethane with a polymerization degree of m=180.
4. The double-layer composite water-repellent protective film according to claim 2 or 3, characterized in that: The mass ratio of the low-polymerization-degree material (I) to the high-polymerization-degree material (II) in the support layer is in the range of 25:75 to 60:
40.
5. A method for preparing a water-repellent protective film having a double-layer composite structure according to any one of claims 1 to 3, characterized in that The following steps are involved: S1, preparation of supporting layer polymer: adding low-polymerization degree material (I) and high-polymerization degree material (II) in proportion to a reactor containing a solvent, heating to 60±10°C and stirring to completely dissolve; then adding methyl methacrylate and a catalyst, heating to 70±5°C, and reacting under nitrogen for 4-8 hours. The obtained product solution is precipitated in anhydrous ethanol, filtered, and vacuum dried to obtain a composite supporting layer polymer; S2, preparation of a water-repellent layer polymer: adding a solvent to a reaction vessel, and under nitrogen protection, adding trimethylsiloxane and perfluorooctyl acrylate in proportion and stirring until completely dissolved, then adding azobisisobutyronitrile (AIBN) as an initiator, and continuously stirring at 70±5°C for 4-8 hours to cause a free radical polymerization reaction. After the reaction is completed, the reaction solution is introduced into petroleum ether for precipitation. The precipitate collected by filtration is washed with petroleum ether several times to remove residual solvent and unreacted monomers, and then vacuum dried to obtain a trimethoxysiloxane-perfluorooctyl acrylate water-repellent layer polymer; S3, pouring the composite supporting layer polymer obtained in step S1 into ethanol, stirring at 40±5°C to completely dissolve it to obtain a supporting layer solution; adding the trimethoxysiloxane-perfluorooctyl acrylate water-repellent layer polymer obtained in step S2 into dichloromethane, stirring at 40±5°C to completely dissolve it to obtain a water-repellent layer solution; slowly adding the water-repellent layer solution to the supporting layer solution under stirring to obtain a protective film composition solution with a solid content of 35-50% and no stratification or precipitation.
6. The method for preparing the double-layer composite water-repellent protective film according to claim 5, characterized in that: In step S1, when the low polymerization degree material (I) is a polycaprolactone oligomer, the solvent is selected as N,N-dimethylformamide (DMF); when the low polymerization degree material (I) is a polylactic acid oligomer, the solvent is selected as dichloromethane; when the low polymerization degree material (I) is a polyurethane oligomer, the solvent is selected as tetrahydrofuran (THF).
7. The method for preparing the double-layer composite water-repellent protective film according to claim 5, characterized in that: In step S1, the catalyst is p-toluenesulfonic acid, dibutyltin dilaurate, and stannous octoate, and the added amount thereof accounts for 0.1-2% of the total mass of the reaction monomers.
8. The method for preparing the double-layer composite water-repellent protective film according to claim 5, characterized in that: In step S2, when synthesizing the water-repellent polymer of structural formula (III), the solvent is selected from ethyl acetate and dichloromethane; when synthesizing the water-repellent polymer of structural formula (IV), the solvent is toluene, xylene, or tetrahydrofuran.
Citation Information
Patent Citations
Water-repellent and oil-repellent anhydride-based fluorine-containing acrylate resin, preparation method and application
CN112500525A
Environment-adaptive water-based durable short-chain fluorine-containing water-repellent and oil-repellent coating as well as preparation method and application thereof
CN118421154A